Pseudo-bilayer architecture enables high-performance organic solar cells with enhanced exciton diffusion length - Kui Jiang (Nature Portfolio, 2021)
The so-called pseudo-bilayer (PB) organic solar cell (OSC) device architecture can promote enhanced exciton dissociation and charge transport, leading to improved device performance. Here, the authors report high-efficiency OSCs that features a PB architecture and optimized ternary system.